Fact-checking: an analysis of the political information verified by the Truco! Project - Conceição, Desirèe Luíse Lopes; Segurado, Rosemary (FCL-UNESP Laboratório Editorial, 2020)
This article aims to analyze the political information produced and disseminated by the digital platform Truco!, which is a Agência Pública fact-checking project developed for the 2014 election, in Brazil. This project, one of the first in the country, verified the presidential candidates’ speeches during the free electoral campaign advertising on television comparing what they said with data and the facts available. The methodology consists of an elaboration for primary data collection, defined upon initial observation of the Agência Pública work. The results recognize qualitative investigative journalism work, showing a process to practice the fact-checking, and the broadening of the political content. Therefore, a counter-information space was built, with the possibility of using the fact-checking to face a recent global phenomenon, the fake news cases.